Epstein-Barr DNA in advanced pediatric nasopharyngeal cancer - Marlinda Adham; Namira Kesuma Jelita; Djajadiman Gatot; Soehartati Argadikoesoema Gondhowiardjo; Lisnawati Rachmadi; Astrid E Greijer; I Bing Tan; Jaap M Middeldorp (Paediatrica Indonesiana, 2021)
Background Studies suggest that the most common type of nasopharyngeal carcinoma (NPC) is WHO-3, which is strongly associated with Epstein-Barr virus (EBV). Objective To assess NPC patient characteristics in a national general referral hospital in Indonesia, with regards to EBV DNA load and treatment response. Methods Twenty-three pediatric patients diagnosed with NPC were included in the study. Data collected were history, physical examination, tissue biopsy, CT scan, staging and EBV DNA load from nasopharyngeal (NP) brushing as well as blood specimens. The NP brushing, blood specimens and CT scan evaluations were done two months post-treatment. Results Pediatric patients with symptoms such as blood tinged secretion, lymph node enlargement, and nasal congestion were more likely to have higher EBV DNA loads in their NP brushings (P<0.05) (including T3 and higher). Despite significant reduction of EBV DNA load in NP brushing post-treatment, it was not associated with treatment response, as evaluated by CT scan. Conclusion Higher DNA load from NP brushings is associated with a higher tumor stage. Larger sample size and follow-up data are needed to assess the usefulness of EBV DNA load assessment in pediatric patients.